Alteration in surface muscle electrical anisotropy in the rat SOD1 model of amyotrophic lateral sclerosis - Li, Jia (2011)
OBJECTIVE: To evaluate the effects of progressive neurogenic change on surface-measured anisotropy via study in the rat superoxide dismutase 1 (SOD1) G93A amyotrophic lateral sclerosis (ALS) model. METHODS: Eight male ALS rats were studied over a period of 10 weeks. In each, the 20 kHz to 1 MHz electrical impedance of the gastrocnemius-soleus complex was measured with electrodes placed at 0° and at 90° relative to the major muscle fiber direction. The major outcome measure, the anisotropy difference (AD) for each of the resistance, reactance, and phase, was calculated as 90° – 0° values. RESULTS: All three parameters showed substantial alterations with disease progression. However, the phase AD demonstrated the most substantial change, increasing from 1.8 ± 1.58° to 10.2 ± 2.13° (mean ± standard error) comparing the first and last set of measurements (p = 0.028). CONCLUSIONS: Anisotropy increases substantially with disease progression in the ALS rat. SIGNIFICANCE: Measurement of surface electrical anisotropy offers a non-invasive means for quantifying neurogenic change in muscle.